PIP4K attenuates PIP5K lipid kinase activity by disrupting membrane-mediated dimerization - Benjamin R. Duewell; Michael Worcester; Michael J. Chirumbolo; Alayna Beam; Samantha M. Fernandez-Ortiz; Gerald R. V. Hammond; Scott D. Hansen (Proceedings of the National Academy of Sciences, 2026)
The phosphatidylinositol 4-phosphate 5-kinase (PIP5K) family of enzymes generate most of the phosphatidylinositol-4,5-bisphosphate [PI(4,5)P 2 ] lipids in eukaryotes. In solution, PIP5K exists in a weak monomer-dimer equilibrium but undergoes membrane-mediated dimerization, which potentiates lipid kinase activity. We hypothesized that mechanisms that regulate PIP5K dimerization could function to buffer lipid kinase activity, thus providing a mechanism for maintaining relatively constant PI(4,5)P 2 levels at the plasma membrane. Due to the transient nature and density dependence of PIP5K dimerization, deciphering how other proteins modulate PIP5K dimerization has not been feasible. To address this limitation, we established a single molecule Förster resonance energy transfer (FRET) assay to visualize membrane-mediated homodimerization and heterodimerization of PIP5K paralogs on supported lipid bilayers using Total Internal Reflection Fluorescence Microscopy. Using this approach, we find that PIP4K attenuates PIP5K lipid kinase activity by disrupting membrane-mediated dimerization. Guided by structure prediction, we generated PIP4K mutants that are unable to disrupt PIP5K membrane-mediated dimerization thus preventing the attenuation of lipid kinase activity. In vivo, mutations that disrupt the PIP4K–PIP5K interaction similarly prevent PIP4K-mediated inhibition of the PIP5K activity. Overall, this work reveals the molecular basis of the PIP4K-mediated inhibition of PIP5K, which has been shown to regulate PI(4,5)P 2 lipid homeostasis. Creation of this PIP5K dimerization FRET biosensor also establishes a tool for deciphering how proteins modulate membrane-mediated dimerization of PIP5K in the future.